Small singlet-triplet energy gap of acridone enables longer wavelength sensitisation of europium(III) luminescence - Dadabhoy, A; Faulkner, S; Sammes, P (2000)
Incorporation of 9(10H)-acridone as a chromophore into a seven-coordinate chelating ligand allows observation of sensitised luminescence from the europium(III) complex, even with excitation wavelengths greater than 410 nm.